2007
DOI: 10.1016/j.jtcvs.2006.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects on the mesenteric microcirculatory response to vasopressin and phenylephrine after cardiopulmonary bypass

Abstract: A differential pattern of mesenteric vasomotor regulation exists after cardiopulmonary bypass that may contribute to the risk of mesenteric ischemia after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
2
20
1
Order By: Relevance
“…Taken together this may lead to visceral organ damage. In addition, CPB has been implicated in causing microemboli, free radical production secondary to ischemia reperfusion injury, splanchnic hypoxia, gastric mucosal acidosis, and mesenteric vasoconstriction 28,36‐38 . These findings support the role of CPB as a cause of GI complications.…”
Section: Pathophysiologymentioning
confidence: 62%
See 1 more Smart Citation
“…Taken together this may lead to visceral organ damage. In addition, CPB has been implicated in causing microemboli, free radical production secondary to ischemia reperfusion injury, splanchnic hypoxia, gastric mucosal acidosis, and mesenteric vasoconstriction 28,36‐38 . These findings support the role of CPB as a cause of GI complications.…”
Section: Pathophysiologymentioning
confidence: 62%
“…It is seen frequently in patients who have hypoperfusion syndrome or are on inotropic pressor support. The pathogenesis of this process is poorly understood but likely involves low cardiac output and diffuse mesenteric vasoconstriction that leads to intestinal hypoxia and possible necrosis 36 . In the absence of peritonitis or unexplained acidosis as an indication for emergency laparotomy, mesenteric angiography remains the gold standard though CT angiogram has become a fast and noninvasive alternative.…”
Section: Off‐pump Cabgmentioning
confidence: 99%
“…Anaesthesia, surgical trauma, anticoagulation, CPB and hypothermia are responsible for triggering stress responses that may result in visceral organ damage. CPB has also been implicated in causing microemboli, increase in intestinal permeability, free radical production through ischaemia‐reperfusion injury, splanchnic hypoperfusion and gastric mucosal acidosis …”
Section: Discussionmentioning
confidence: 99%
“…Conversely, coronary microvascular relaxation responses to adenosine diphosphate (ADP), an endothelial-dependent vasodilator, are unchanged after CP, suggesting the up-regulation of VEGF receptors on the coronary endothelium is selective and may play a role in mediating perioperative increases in vascular permeability. Porcine studies involving CP/CPB have demonstrated increases in VEGF in the lungs after CPB, possible contributing to the post-operative lung edema observed in patients after CPB (65). The increases in circulating levels of VEGF after CP/CPB have been correlated with clinical cardiovascular impairments, as well as the development of capillary leak syndrome (1, 21).…”
Section: Growth Factorsmentioning
confidence: 99%